NIR-fluorescent dye doped silica nanoparticles for in vivo imaging, sensing and theranostic. (13th March 2018) - Rampazzo, Enrico; Genovese, Damiano; Palomba, Francesco; Prodi, Luca; Zaccheroni, Nelsi
Abstract: The development of nanostructures devoted to in vivo imaging and theranostic applications is one of the frontier fields of research worldwide. In this context, silica nanoparticles (SiO2 -NPs) offer unquestionable positive properties: silica is intrinsically non-toxic, several versatile and accessible synthetic methods are available and many variations are possible, both in terms of porosity and functionalization for delivery and targeting purposes, respectively. Moreover, the accumulation of several dyes within a single nanostructure offers remarkable possibilities to produce very bright and photostable luminescent nanosystems. Advancements in imaging technology, bioassay, fluorescent molecular probes have boosted the efforts to develop dye doped fluorescent SiO2 -NPs, but despite this, only a quite limited set of systems are applicable in vivo . Herein we discuss selected examples that appeared in the literature between 2013–17, with imaging capabilities in vivo and characterized by a significant near infrared (NIR) fluorescence emission. We present here very promising strategies to develop SiO2 -NPs for diagnostic and therapeutic applications—some of which are already in clinical trials—and the possibility to develop bio-erodable SiO2 -NPs. We are convinced that all these findings will be the basis for the spread of SiO2 -NPs into clinical use in the near future.